Effect of yearly milk per cow on profitability of dairy herds - Edward P. Call; James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1993)
An analysis of Kansas Holstein herds in 1992 indicated that the yearly milk production per cow had a significant effect on returns to labor and management. The lowest quartile herds (13,445 lb per cow average) had a negative return to management. Herds averaging 20,614 lb per cow yielded $479 return to management. Records become increasingly important in managing the dairy operation, especially those that are readily analyzed and predict the degree of economic change when management is modified.; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; Dairy; Milk production; Profit; Dairy cattle